Design of Watering Tools for NodeMCU-Based Palm Seedlings: Rancang Bangun Alat Penyiraman Bibit Kelapa Sawit Berbasis NodeMCU - Rio Rilandani; Wahyu Prima; Raimon Efendi (Journal of Vocational Education and Information Technology (JVEIT), 2020)
The purpose of this research is how to make a nodemcu-based palm oil seeding tool at the Sitiung Experimental Garden Agriculture Agency so that the water needs are fulfilled so that the water content can be properly fulfilled, the more water content is found in plants, the better the growth and development of seedlings , thus with regular watering, and water content being met, the resulting seeds are of high quality and superior. There are also problems that researchers found at the Sitiung Experimental Garden Agricultural Agency, where watering oil palm seedlings is still using manual tools, and farmers also have limited resources and time farmers have to carry out maintenance / watering plants that require a long and complicated process, of course, things This really requires a technological system that is able to accommodate all matters related to the automatic watering of oil palm plants using a cellphone as a controller. So the solution of the problem raised by researchers with the rapid growth of technology in agricultural technology, especially in oil palm nurseries, researchers want to make a tool that is very helpful and facilitate farmers in caring for oil palm seedlings. So that the level of water needed by palm oil is fulfilled, so this will greatly affect the growth and fertility of palm seedlings and plant growth. The results of this study are a nodemcu-based palm seedling watering tool which greatly facilitates the Sitiung Experimental Garden Agricultural Agency in watering palm oil seedlings so that the nurseries run well and produce superior seeds.